Biopolymers Online 2002
DOI: 10.1002/3527600035.bpol6001
|View full text |Cite
|
Sign up to set email alerts
|

Pullulan

Abstract: Introduction Historical Outline Chemical Structure Physiological Function Chemical Analyses Occurrence Biosynthesis Culture Conditions and Cell Morphology Biosynthetic Mechanism Genetics and Molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 228 publications
0
22
0
Order By: Relevance
“…Strain variability plays an important role in determining how biosynthesis proceeds, and factors such as carbon source, cell morphology, oxygen concentration, temperature, shear stress (i.e., in a fermentor), and trace amounts of vitamins and minerals all affect pullulan production. 1 Some studies have shown that pullulan is produced more in stationary, compared to exponential-phase, growth. 6,57 This is consistent with the idea that pullulan is a secondary metabolite, and so it is produced only when growth decreases, although by a strict definition, secondary metabolites refer to diffusible products, and thus pullulan would not be such a compound.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Strain variability plays an important role in determining how biosynthesis proceeds, and factors such as carbon source, cell morphology, oxygen concentration, temperature, shear stress (i.e., in a fermentor), and trace amounts of vitamins and minerals all affect pullulan production. 1 Some studies have shown that pullulan is produced more in stationary, compared to exponential-phase, growth. 6,57 This is consistent with the idea that pullulan is a secondary metabolite, and so it is produced only when growth decreases, although by a strict definition, secondary metabolites refer to diffusible products, and thus pullulan would not be such a compound.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is frequently categorized as a mild plant pathogen, particularly for grapes, and plays a vital role in the post-harvest decay of many crops. A. pullulans is also an opportunistic human pathogen, especially in immuno-compromised hosts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aureobasidium proteae was reported to cause chronic fungal meningitis (Kutleša et al, 2012) as well as a leaf spot disease of Proteaceae (Crous et al, 2011). Some isolates of A. pullulans produce semiochemicals (Davis et al, 2012) that influence wasp behaviour in nature and that may be involved in dispersal of members of the genus Aureobasidium, while other isolates produce large amounts of the extracellular polysaccharide (EPS) pullulan (Manitchotpisit et al, 2009), a polysaccharide with many valuable industrial and medical uses (Leathers, 2002;Cheng et al, 2011). Still other isolates biosynthesize products that have commercial value such as laccase (Rich et al, 2011), xylanase (Manitchotpisit et al, 2009) or poly b-L-malic acid (Manitchotpisit et al, 2012).…”
mentioning
confidence: 99%